Rapid diagnosis of bovine brucellosis by peptide nucleic acid-fluorescence in situ hybridization assay - LAKSHMIKANTH, K S; SHARMA, N S; KAUR, PAVITER; PATHAK, D; ARORA, A K (The Indian Journal of Animal Sciences, 2022)
Brucellosis is a major economical disease of livestock and an important zoonotic disease. Rapid and accurate diagnosis is a fundamental prerequisite in the quest for control and elimination of brucellosis. The current study was conducted to evaluate a rapid molecular technique, peptide nucleic acid-fluorescence in situ hybridization (PNA-FISH) assay for the diagnosis of brucellosis. Samples, including fetal stomach contents, vaginal discharges, and placenta collected from cattle and buffaloes experiencing abortion and other reproductive disorders were processed for isolation. Brucella isolates obtained were confirmed by biochemical tests and polymerase chain reaction (PCR), thereby subjected to PNA-FISH which yielded positive fluorescence. The clinical samples were processed and subjected directly to PNA-FISH. On performing PNA-FISH directly on the clinical samples, this test reduces the time spent on processing the sample for isolation, avoiding the risk of handling the infectious organism while going through the process of isolation. Hence, PNA FISH can be considered as a rapid and efficient diagnostic method for Brucellosis.